Comparison of specific expression profile in two in vitro hypoxia models - Calvo Anguiano, Geovana; Lugo Trampe, José de Jesús; Camacho Morales, Alberto; Said Fernández, Salvador; Mercado Hernández, Roberto; Zomosa Signoret, Viviana Chantal; Rojas Martínez, Augusto; Ortiz López, Rocío (2018)
Abstract. The microenvironment plays a fundamental role in carcinogenesis: Acidity and hypoxia are actively involved in this process. It is important to have in vitro models to study these mechanisms. The models that are most commonly referred to are the hypoxia chamber and the chemical induction [Cobalt (II) chloride]. It is not yet defined if these models are interchangeable if the metabolic effect is the same, and if the results may be compared in these models. In the present study, the response to the effect of stress (hypoxia and acidity) in both models was evaluated. The results indicated that in the chemical model, the effect of hypoxia appeared in an early form at 6 h; whereas in the gas chamber the effect was slow and gradual and at 72 h there was an overexpression of erythropoietin (EPO), vascular endothelial growth factor (VEGF), carbonic anhydrase 9 (CA9) and hypoxia-inducible factor 1α (HIF1α). In addition to the genes analyzed by reverse transcription-quantitative polymerase chain reaction, the global expression analysis between both models revealed the 9 most affected genes in common. The present study additionally identified 3 potential genes (lysyl oxidase, ankyrin repeat domain 37, B-cell lymphoma 2 interacting protein 3 like) previously identified in other studies, which may be considered as universal hypoxia genes along with HIF1α, EPO, VEGF, glucose transporter 1 (GLUT1), CA9, and LDH. To the best of the author's knowledge, this is the first time that both hypoxia models have been compared, and it was demonstrated that the effect of hypoxia induction was time sensitive in each model. These observations must be considered prior to selecting one of these models to identify selective hypoxia genes and their effects in cancer.